Exotic viral infections in primary healthcare: a case report of chikungunya in a patient returning from tropical regions - Gilewska, Anna; Wierzbicka, Agnieszka; Aksak-Wąs, Bogusz (Lekarz POZ, 2025)
Tropical diseases such as chikungunya are increasingly reported in Europe due to globalization and rising human mobility. We present a case of a 50-year-old female patient who, after returning from Cuba, visited her primary care physician with fever, severe joint pain, and rash. Serological testing confirmed chikungunya virus infection. The treatment was symptomatic, and the patient’s condition improved within two weeks. Increased travel to endemic regions raises the risk of introducing tropical diseases. Early diagnosis is crucial for appropriate management and prevention of complications. Primary care physicians should consider tropical diseases in the diagnostic workup of patients returning from travel to exotic countries.